Analysis of the Impact of Basic Technique Training on Increasing Shooting Accuracy and Ball Handling in Basketball Players: A Literature Review - Ahmad Hidayat; Bribert Martua Panggabean; Vebrianto Valentino Purba; Toto Haryono Tumanggor; Tori Budi Tomo Siahaan; Deni Rahman Marpaung (Badan Penerbit STIEPARI Press, 2025)
This study is motivated by the importance of mastering basic techniques in basketball, especially in improving shooting accuracy and ball handling skills. The purpose of this study is to analyze the impact of basic technique training on improving these two aspects of skills. The method used is a literature review of ten scientific journals published from 2020 to 2025 that are relevant to the topic. The results of the analysis show that basic technique training consistently makes a positive contribution to improving shooting accuracy and ball handling skills in basketball players, both at beginner and advanced levels. This finding reinforces the importance of implementing a structured and sustainable basic technique training program in athlete development. The implications of this study point to the need for coaches and policy makers in sports to integrate basic technique training as a core part of the basketball training curriculum.